Treatment or Else: Coerced Treatment for Drug-Involved California Parolees. (July 2013) - Zhang, Sheldon X.; Roberts, Robert E. L.; Lansing, Amy E.
This study evaluated a community-based correctional program in California, in which parolees tested positive on illicit drugs were given the option of going into a treatment program or having their parole revoked and returned to prison in California. Two comparison groups were constructed to assess the treatment effect—a propensity-based comparison group extracted from the general parolee population and program dropouts. Although implicitly coercive, some parolees who finished the program were less likely to be reincarcerated 12 months following release than both comparison groups. However, the observed treatment advantage quickly eroded in the second observation year. Savings realized from the incarcerations avoided were more than enough to pay for the program. Findings from this study suggest that boosting participation in reentry services through coercive measures may yield currently unrealized individual and societal benefits. However, systemic efforts are needed to extend the short-term treatment effects. Design and data limitations in the study weaken the persuasiveness of these findings. Methodological implications and policy issues about coerced treatment are discussed.